2016
DOI: 10.1186/s12885-016-2653-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and resource use of implementing MRI-guided NACT in ER-positive/HER2-negative breast cancers in The Netherlands

Abstract: BackgroundResponse-guided neoadjuvant chemotherapy (RG-NACT) with magnetic resonance imaging (MRI) is effective in treating oestrogen receptor positive/human epidermal growth factor receptor-2 negative (ER-positive/HER2-negative) breast cancer. We estimated the expected cost-effectiveness and resources required for its implementation compared to conventional-NACT.MethodsA Markov model compared costs, quality-adjusted-life-years (QALYs) and costs/QALY of RG-NACT vs. conventional-NACT, from a hospital perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Finally, besides standardization and validation issues, there are also limited data about the cost-effectiveness of MRI in the NST setting [ 63 ]. To get an overall idea of the added value of DWI in this NST setting, also cost-effectiveness needs to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, besides standardization and validation issues, there are also limited data about the cost-effectiveness of MRI in the NST setting [ 63 ]. To get an overall idea of the added value of DWI in this NST setting, also cost-effectiveness needs to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that DES modelling is not a prerequisite for capturing the effect of constraints via throughput measuresapproaches that predominate in HTA such as cohort-based state transition models (such as Markov models) and decision tree models can be used for estimating overall resource requirements. Two such studies reported the use of Markov modelling to estimate the resources required in order to estimate the feasibility of the respective programmes [41,42].…”
mentioning
confidence: 99%